Efektivitas Video Tutorial untuk Meningkatkan Keterampilan Vokasional Membuat Souvenir Anak Berkebutuhan Khusus - Gustika Sari, Kena (Journal of Special Education Lectura, 2024)
This research is motivated by the problem of a mild mentally retarded child who has very low skills to make souvenirs so that there is a need for teaching to improve the skills of mild mentally retarded children so that they are proficient in making souvenirs so that this can be a provision for children in the future and can be competent in the world of work. The purpose of this research is to prove video tutorials in improving the ability to make souvenirs from handkerchiefs at SLB Muhammadiyah Nanggalo Padang. The type of research used is single subjek research with the A-B-A design. Baseline A1 condition consists of four meetings, the intervention condition consists of seven meetings and the second baseline condition consists of three meetings. The method used in data collection in this study was recording events by collecting data when children made souvenirs from handkerchiefs. Based on direct observation, the data were analyzed using visual and graphic analysis. The results of the study stated that the video tutorial for making souveni from handkerchief towels can improve vocational skills during the learning process and aims for survival in the future.